Biodegradable membrane of poly(l-lactide acid-dioxanone-glycolide) and stereocomplex poly(lactide) with enhanced crystallization and biocompatibility - Fan, Tiantang; Qin, Jingwen; Meng, Xiao; Li, Jiafeng; Liu, Qing; Wang, Guannan (Frontiers in Bioengineering and Biotechnology, 2022)
The mebranes of poly(L-lactide acid-p-dioxanone-glycolide) (PLPG) with stereocomplex poly(lactic acid) (sc-PLA) were prepared by the solution blending way. It was observed that sc-PLA significantly heightened the crystallizing behavior of PLLA segments of PLPG metrix. And, the crystallizing behavior displayed that the temperature of crystallization shifted to a higher range than that of the PLPG. Moreover, half-time of crystallization sharply decreased in value as sc-PLA content increased in value on account of the pre-eminent nucleation ability of sc-PLA. TGA results revealed the thermal stability of the samples with the increase of sc-PLA compared to PLPG. Meanwhile, enzymatic degradation results indicated the mass loss rate of the mebrane decreased as the introduction of sc-PLA, but the overall degradation ability was still greater than that of PLLA. In the meantime, the biological experiment indicated that the mebrane possessed low cytotoxicity.